PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN INTERAKTIF PADA MATERI PERUBAHAN WUJUD BENDA DI SD NEGERI 2 PEUSANGAN SELATAN - Mohd. Jericho; Fatma Zuhra; Sari Rizki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low learning outcomes of fifth-grade students in the Natural and Social Sciences (IPAS) subject on the topic of changes in the state of matter at SD Negeri 2 Peusangan Selatan, with an initial classical completeness percentage of only 60%. This study aimed to improve teacher activity, student activity, and student learning outcomes through the implementation of an interactive learning model that actively engages students through question-and-answer sessions, group discussions, presentations, and the completion of student worksheets. This research was a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages, involving 20 fifth-grade students as subjects. Data were collected through observation of teacher and student activities, student worksheets, and learning outcome tests, then analyzed descriptively using percentage formulas for completeness and activity scores. The results showed that teacher activity increased from 89.29% (good category) in Cycle I to 100% (very good category) in Cycle II, student activity increased from 78.00% (good category) to 88.20% (very good category), and the percentage of learning completeness based on the Learning Objective Achievement Criteria increased from 75% in Cycle I to 90% in Cycle II. It can be concluded that the interactive learning model is effective in improving learning activities and student learning outcomes on the topic of changes in the state of matter in elementary school.